Evaluasi Implementasi Program Rumanis Datang Si Kumis Hilang sebagai Upaya Mengatasi Kemiskinan Ekstrem di Kabupaten Wonogiri - Putri, Masykurotur Rizqi Aji; Al-Azkiya, Muhammad Emir; Dewanto, Bambang; Dimara, Yemima Inanse Orpa; Wahyunengseh, Rutiana Dwi; Mulyadi, Asal Wahyuni Erlin (Kolaborasi : Jurnal Administrasi Publik, 2025)
The alleviation of extreme poverty is one of the main focuses of the Wonogiri Regency Government. Data from Bapperida Wonogiri in 2024 show that there were 136,799 heads of households or 497,154 people, included in the extreme poverty category in Wonogiri. This study aims to assess the success of the implementation of Rumanis Datang Si Kumis Hilang program as a manifestation of the Wonogiri Regency Government’s commitment, particularly the Public Housing, Settlement Area, and Land Service in addressing extreme poverty by providing habitable housing. Additionally, the study seeks to assessing the results of implementation evaluation within the Rumanis Datang Si Kumis Hilang program. The research method that used in this research is qualitative, using a case study approach. The study’s results indicate that the Rumanis Datang Si Kumis Hilang program has been successful, as evidenced by the achievement of its objectives. In general, two out of the three objectives of this program can be considered successful (1) the provisioun of stimulus funds to low-income communities, which was supported by various stakeholder and (2) a reduction in the number of uninhabitable houses (RTLH) in Wonogiri every year. However, despite the success, several shortcomings need to be addressed to maximize the impact to the community. These include funding sources, which are still considered insufficient for home repairs, despite support from multiple stakeholders, post-implementation monitoring of the program, and the need to increase the number of Field Facilitator members (TFL) to enhance the program effectiveness.